Impact of public and private sector external debt on economic growth - Silva, Jorge (2018)
We assess the effect of the Portuguese external debt of the private and public sectors on economic growth for the period 1999-2014. We study the channels through which external debt may affect economic growth: demand, supply and external accounts. Regarding aggregate demand, we evaluated private saving, public investment in volume and real GDP per person employed. The external debt of the public sector showed some evidence of having a detrimental influence on private saving, but a favourable effect on public investment in volume. The gross external debt of the private sector positively influenced public investment. Concerning aggregate supply, we analysed the production function per person employed in the private sector. Private external debt positively affected the gross value added in volume per person employed. Public external debt negatively impacted the gross value added in volume per person employed and the total factor productivity. Regarding external accounts, the private external debt affected the primary income account, though it had a low coefficient.